Exploration of the Teacher’s Competence in the New Competency Based Curriculum in the Selected Schools in Rukiga District. - Akatwijuka, Martha (Kabale University, 2025)
The study assessed the exploration of teachers' competence in the new competence-based curriculum in Rukiga District. The objectives of the study were to find out if Teachers have the necessary competencies to teach based curriculum and to find out possible remedies of competence curriculum in Rukiga District. A descriptive research design was used and data was collected using questionnaires and interviews. The study results on the impact of self-esteem among students in the study of teachers' competence in the new competency-based curriculum. The highest number of respondents mentioned that the new competence-based curriculum helps teachers to improve their teaching and assessment. The study results on challenges faced by Teachers in Teaching new curriculum. The highest number of respondents mentioned the provision of a conducive environment that builds the relationship between teachers and learners for better results of the new curriculum. The least number of respondents mentioned that students need to be active in the learning of the new curriculum. The study recommended researchers use the available information about the teachers and find out how they find it hard to show commitment to the new competence based curriculum.